Is Virtualization at Present a Cloud Science? (2018)
Introduction: The present research was conducted in 2017 at Raiganj University, India. Cloud Computing and virtualization are significant concepts in today’s computing and information technology world. Cloud Computing is helpful for creating eco-friendly atmospheres, in other words, complete and healthy sustainability. Academic programs in the field of virtualization and Cloud Computing are still rare. This study seeks to learn more about such affairs.Methods: Cloud Computing is actually a kind of virtualization which ultimately helps create virtual platforms, thus it is useful to learn about various educational programs in the field, the methods of general search engine have been used with proper keywords and titles.Result: Cloud Computing and its wider uses resulted in academic programs, centers and departments in many countries around the world. Cloud Computing forms a tool and mechanism of virtualization for complete scientific domain nowadays. Virtualization has become a field and an available study program in international universities and also in Indian academics.Conclusions: This paper highlights several aspects of Cloud Computing from the beginning to growing nature as a field of study with academic and techno-managerial points of view.Originality: In major indexing agencies, studies on Cloud Computing are rarely available in Indian context.Limitation: The study concerned a specific area in India and used search methods conducted from July to September 2017. After that period, work has not been included and analyzed in the study.